Editorial: Towards 2030: Sustainable Development Goal 1: No Poverty. A Sociological Perspective - Grzegorz Piotr Gawron; Piotr Toczyski (Frontiers in Sociology, 2024)
This Research Topic focuses on the first Sustainable Development Goal (SDG) by the UN, which aims to “end poverty in all its forms everywhere.” Progress toward this goal is evaluated through various targets and indicators. The most recent SDG progress report highlighted how poverty reduction has significantly slowed and worsened, mainly due to the COVID-19 pandemic (United Nations, 2024). This unprecedented emergency has particularly affected informal workers, young people, and women. With the goal of eradicating poverty by 2030 currently off track, intensified action is crucial. Moreover, amid a growing climate crisis, significant efforts are needed to bring the 2030 targets within reach. This Research Topic examines SDG1 from a sociological perspective, focusing on its framing, geographic adaptations, stakeholder involvement, and the influence of social mobility and stratification studies, especially in the context of the challenges of the post-COVID-19 pandemic.
Keywords: P46; I30; H75; 330; SDG1; COVID-19; poverty; injustice; resilience; sustainable development